Continuous variable quantum key distribution protocol with Gaussian and non-Gaussian modulations - Becir, Ahmed (Kulliyyah of Science, International Islamic University Malaysia, 2012)
Quantum key distribution (QKD) involves generating cryptographic keys using quantum states at both ends of the communicating parties (Alice and Bob). Any attempt to eavesdrop on the transmission will, necessarily by the laws of quantum mechanics, disturb or destroy the states. By identifying and only using keys that have not been disturbed, a perfectly secure cryptographic system can be realized. Discrete variable QKD was proposed in 1984 by Bennett and Brassard. Since then attempts to exploit this technology have been beset with the difficulties of working with the discrete variables in question - single photon states. Recently, the idea of continuous variable QKD was developed, in which the information-carrying quantum states are properties of a bright continuous wave laser beam. Bright laser beams are relatively simple to manipulate and can carry large amounts of information even when subject to high loss. This method however also suffers from the limited distance due to the noises introduced by the quantum channel. Continuous variable QKD protocols based on coherent state modulation are theoretically limited to 50 Km. In this thesis we introduce two new continuous variable protocols: The first one is based on the Gaussian modulation of entangled squeezed coherent state. The idea is instead of using maximally entangled state we choose to use weakly entangled state since the latter one is more robust to the quantum channel losses. However, using weakly entangled states makes the former security proofs (that are based on the Heisenberg uncertainty and Holevo quantity) no more efficient, in which we cannot drive tight bounds on the eavesdropper's accessible information. For this purpose we use the decomposition of the real symplectic matrix to derive tight upper bounds for eavesdropping individual and collective attacks. This protocol shows high promise in term of achievable distance, noise tolerance and key rate. It also shows that breaking the 50Km with sufficient key rate is possible. The second protocol is based on the discrete modulation (non Gaussian modulation) of the coherent (phase coherent) states, in which we introduce three different types of this protocol namely 2-states, 4-states and 8-states protocol. The 8-states protocol shows high tolerance against the channel noises and it can achieve hundreds of kilometers distance in fiber optics.